The role of sectoral policies in the energy transition - Pinkas, Aleksandra (Wydawnictwo Uniwersytetu Wrocławskiego, 2023)
The objective of this paper will be firstly to indicate the significance of sectoral policies, as well as to explain the impact of cross-sectoral policies on the achievement of their goals. Next, these considerations will be related to the role of energy sectoral policies in the energy transition process, taking into account the impact of the cross-sectoral climate policy. The article is directed at highlighting the need to distinguish between sectoral and cross-sectoral policies and to identify the relation between these policies, which has special significance in relation to the energy sector. In order to realise the adopted objective, an administrative-legal research method will be applied, taking into account the perspective of EU law in connection with the significant impact of EU policies on the setting of national sectoral policies.
Keywords: sectoral policy; climate policy; energy policy; energy transition